Drawing on the Ride Side of the Brain - Edwards Betty (Harper Collins Publishers, 1993)
If you want to draw well but think you have no talent, this book will unlock the artist within you and open up a new world of creative enjoyment. Preface, Drawing the Art of Bicycle Riding, Expressing Yourself in Drawing: The Nonverbal Language of Art, Drawing on Memories: Your History as an Artist, Relationships in a New Mode: Putting Sighting in Perspective, The Value of Logical Lights and Shadows, The Zen of Drawing: Drawing Out the Artist Within, Post scrip, Glossary, Bibliography, Index.